Maintaining excellence: the preservation and development of specialised services. - Donaldson, L. J. (1992)
The advent of the Tomlinson inquiry draws attention to the need to strike a balance between market led and planned approaches to health care delivery. This is important not just for hospital rationalisation but also for the preservation and development of services which are provided in a smaller number of hospitals. Specialised services are often in the forefront of raising standards of care and introducing new developments and innovations. They are the only option for a small number of patients with serious illnesses. In the internal market for health care provision created by the 1990 NHS reforms more sophisticated and flexible mechanisms must be found to provide stability for specialised services while at the same time enabling the benefits of purchaser choice and provider competition to be realised.